1991
DOI: 10.1139/b91-251
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and partial purification of phytotoxins from liquid cultures of Leucostoma cincta and Leucostoma persoonii

Abstract: Phytotoxins from Leucostoma persoonii and Leucostoma cincta were isolated by sequential ultrafiltration of cell-free culture filtrates through a series of exclusion membranes. Phytotoxic activity, characterized by stem necrosis and leaf wilt, chlorosis, and necrosis, was evident when a cold acetone precipitate from the < 1000-Da fraction was tested in a peach shoot tip bioassay. Analytical polyacrylamide isoelectrofocusing of the < 1000-Da fraction in the pH range 3.5–6.0 identified two peptide bands at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Among the 47 secondary metabolism gene clusters, 40% are subjected to gene/transposon insertions or losses in at least one genome. Previous reports showed that phytotoxic small polypeptides secreted by the closely related peach canker pathogens Leucostoma persoonii and Leucostoma cincta can only induce stem necrosis on host plants (Svircev et al, 1991). Some of the Valsa spp.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 47 secondary metabolism gene clusters, 40% are subjected to gene/transposon insertions or losses in at least one genome. Previous reports showed that phytotoxic small polypeptides secreted by the closely related peach canker pathogens Leucostoma persoonii and Leucostoma cincta can only induce stem necrosis on host plants (Svircev et al, 1991). Some of the Valsa spp.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of six pectinase genes significantly reduced virulence of V. mali ( Yin et al, 2015 ). Phytotoxic small polypeptides secreted by the closely related peach canker pathogens Leucostoma persoonii and L. cincta can only induce stem necrosis on host plants, reflecting a host specific characteristic ( Svircev et al, 1991 ). In addition, V. mali also possesses homologs of necrosis-inducing factors including NPP1, Ecp2, and Epl ( Yin et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%